2020
DOI: 10.3389/fphys.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Myokine Concentrations After Acute Exercise in Non-obese and Obese Sedentary Women

Abstract: Exercise and physical activity levels influence myokine release from skeletal muscle and contribute to circulating concentrations. Indeed, many myokines, including interleukin (IL)-6, IL-15, secreted protein acidic rich in cysteine (SPARC), and fibroblast growth factor (FGF) 21 are higher in the circulation after an exercise bout. Since these peptides modulate muscle metabolism and can also be targeted toward other tissues to induce adaptations to energy demand, they are of great interest regarding metabolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…Plasma concentrations of FGF21, IL-6, IL-8, IL-15, and IL-18 were regulated by acute exercise. This results confirm the results of others concerning exercise regulation of circulating myokines while providing insight into the time course of myokine release in circulation after an acute exercise bout and the differences in circulating myokines after exercise in women with or without obesity ( Garneau et al, 2020 ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Plasma concentrations of FGF21, IL-6, IL-8, IL-15, and IL-18 were regulated by acute exercise. This results confirm the results of others concerning exercise regulation of circulating myokines while providing insight into the time course of myokine release in circulation after an acute exercise bout and the differences in circulating myokines after exercise in women with or without obesity ( Garneau et al, 2020 ).…”
Section: Introductionsupporting
confidence: 90%
“…The concentration of myokines in the blood after exercise in people with diabetes differs from that in healthy volunteers. In research Garneau et al (2020) it was found that plasma IL-8 and SPARC levels were reduced in the group of women with obesity, whereas plasma IL-13 concentrations were elevated in comparison to non-obese women both before and after the exercise bout. Also was found that plasma FGF21 concentration during the 24 h following the bout of exercise was regulated differently in the non-obese in comparison to obese women.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, IL-6 levels increased after acute strenuous exercise, i.e., a wheelchair marathon [ 153 , 154 ]. A recent study showed that plasma IL-6 levels are closely related to obesity, microglial function, and lactate production [ 155 , 156 , 157 ]. Pedersen et al have published several studies on the relationship between exercise and IL-6 levels in great detail [ 19 , 158 , 159 ].…”
Section: Myokinesmentioning
confidence: 99%
“…Indeed, beyond the known implications of SPARC in wound healing and tissue repair [4,5], this gene was characterized (for the first time) as an exercise-induced gene [6] and also as an electrical pulse stimulation (considered as an in vitro model of exercise)-induced gene in muscular cells [7]. Moreover, SPARC secretion is induced by exercise [8][9][10] after which the concentrations of myokines (including SPARC, interleukin 6 and fibroblast growth factor) increase in the circulation [11]. Therefore, we hypothesize that at least some of the exercise benefits and biological consequences, mainly the muscular phenotype adaptation to exercise, would be mediated by SPARC or the pathways it controls.…”
Section: Secreted Protein Acidic and Rich In Cysteine As An Exercise-induced Genementioning
confidence: 99%